Structure of presented stimuli influences gazing behavior and choice. (July 2020) - Gere, Attila; Danner, Lukas; Dürrschmid, Klaus; Kókai, Zoltán; Sipos, László; Huzsvai, László; Kovács, Sándor
Highlights: Product types affected the majority of the eye-movement variables. Orientation of stimuli influenced time to first fixation and first fixation duration. Stimulus size influenced fixation and dwell count. Decision time increased over 5 and 6 alternatives. Abstract: Well-structured stimuli presentation is essential in eye-tracking research to test predefined hypotheses reliably and to conduct relevant gazing behavior studies. Several bottom-up factors associated with stimuli presentation (such as stimuli orientation, size etc.) can influence gazing behavior. However, only a small number of scientific papers address these factors in a sensory and consumer science context and thus provide guidance to practitioners. The two presented eye-tracking studies on food images aimed at evaluating the effect of the bottom-up factors stimulus size, background of the picture, orientation of food product presentation, the evaluated products and the number of alternatives . Significant effects of product group were found in the case of all eye-movement parameters except time to first fixation and first fixation duration . In contrary, orientation significantly influenced only the time to first fixation and first fixation duration parameters. Stimulus size significantly increased fixation and dwell count, while background showed no significant effects. Furthermore, significant relationships were found between the number of presented images and eye-movement and decision time . Less time was needed in 2AFC (alternative forced choice test), 3AFC and 4AFC and significantly more time was needed to choose one alternative out of 7AFC and 8AFC. The results of the two studies show that the investigated bottom-up factors can significantly influence gazing behavior, and therefore need to be carefully considered when planning or comparing results of eye-tracking experiments.